Peer-to-peer physician feedback improves adherence to blood transfusion guidelines in the surgical intensive care unit. Issue 1 (July 2015) - Yeh, Daniel Dante; Naraghi, Leily; Larentzakis, Andreas; Nielsen, Nathan; Dzik, Walter; Bittner, Edward A.; Chang, Yuchiao; Kaafarani, Haytham M.A.; Fagenholz, Peter; Lee, Jarone; DeMoya, Marc; King, David R.; et al.
Abstract : BACKGROUND: Translation of evidence to practice regarding adherence to published guidelines for transfusion of red blood cells (RBCs) in critically ill patients is sometimes suboptimal. We sought to use a multimodal intervention founded on peer-to-peer feedback and monthly audit to increase adherence to restrictive RBC transfusion guidelines. METHODS: We conducted a prospective interventional study with a preintervention and postintervention comparison in our tertiary care center. For the 6-month preintervention period (January 1, 2013, to June 31, 2013) and the 6-month postintervention period (October 1, 2013, to March 31, 2014), all RBCs transfused in the surgical intensive care unit (SICU) were evaluated for pretransfusion hemoglobin (Hgb) trigger (TRIG). During the intervention, if stable low-risk patients were transfused outside of restrictive guidelines, the clinicians received e-mail notification and education from a surgeon colleague within 72 hours of transfusion. The mean TRIG, percentage of transfusions with TRIG greater than 8.0 g/dL, and rate of overtransfusion (posttransfusion Hgb > 10) were compared before and after intervention. RESULTS: For stable, low-risk patients, mean TRIG decreased from 7.6 g/dL to 7.1 g/dL ( p < 0.001) and percentage of transfusions with TRIG greater than 8.0 g/dL decreased from 25% to 2% ( p < 0.001) The overtransfusion rate decreased from 11%to 3% ( p = 0.001). Total 6-month transfusions decreased from 284 U to 181 U, a 36% decrease. There were no significant differences in median SICU or hospital lengths of stay. Although SICU discharge Hgb and hospital discharge Hgb were significantly lower in the intervention period (8.4 vs. 8.6 [ p = 0.037] and 8.6 vs. 9.0 [ p = 0.003]), 30-day readmission and mortality rates were similar. CONCLUSION: A blood management program based on peer e-mail feedback was effective in improving adherence to guideline recommendations for transfusion of RBCs in stable, low-risk SICU patients. LEVEL OF EVIDENCE: Therapeutic/care management study, level IV.